(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Ascaris lumbricoides is usually refer to a largest one of intestinal nematodes and the most common helminthic parasite that parasitizing humans and cause illness known as ascariasis. The disease is cosmopolitan worldwide and high prevalent throughout tropics and subtropics areas. Prevalence data suggests that 1 billion people are affected with ascariasis . Life cycle of Ascaris lumbricoides has no intermediate or reservoir hosts .life cycle consist of three stages they are egg, larvae and adult stage of which larvae and adult are pathogenic stages while the egg considered infective stage. The parasite transmitted mainly by oral –fecal route. Pathogenicity of Ascaris lumbricoides occurs due to absorption of nutrition from intestinal content of host or by mechanical blockage of intestinal lumen because of large size of worms also the migration of larval stage though the body of host cause many symptoms especially ascaris pneumonia . The best method for identification of parasite is visualized of eggs during exam the stool sample of patient microscopically also detection of adult stage from fecal or vomitus material . Ultrasound are also helpful in case of pancreatic ascariasis or hepatobiliary ascariasis , ascariasis can be treated by both mebendazole and lbendazole as good medications against Ascaris lumbricoides worm .